Challenges of Financial Management of the Higher EducationInstitutions in Georgia - Kasradze, Tea; Antia, Vakhtang; Gulua, Ekaterine (European Journal of Economics and Business Studies, 2022)
The funding of the higher education institutions and its efficient managementaffects the functioning of the whole system. The level of development of aneducation and science has an important role in the economic development ofthe country. Georgia has enough potential to achieve economic developmentby intellectual and educated human resources. Despite the reformsimplemented in the recent years, there are still many shortcomings andchallenges left in the education system that are hindering the creation of welleducatedand competitive human resources. Without strengthening theeducation system, it is impossible to participate in a global competition. Theincreasing of financing of the education system over the years does not meanraising the quality of education. Developing the correct strategy and tactics ofthe reform and adequate and efficient distribution of financial resources iscrucial. The aim of the paper is to study impact of the existing funding policyon higher education system in Georgia. The structure and dynamics of thefunding of the higher education institutions, the nature and importance of thealready funded projects are examined in the study. The issue of promotion ofdevelopment of education through the reforms implemented in the educationsystem is also discussed and analyzed in it. The study is based on thequalitative and quantitative analyses. The recommendations issued withinthe framework of the study will support stakeholders to overcome the current challenges and improve financial management policy of higher education institutions.
Keywords: Financing of higher education institution, financial management